Effects of process parameters and thermo-mechanical simulation of gas metal arc welding process. (1st October 2016) - Kamble, A. G.; Venkata Rao, R.
Abstract: The gas metal arc welding is a fusion welding consisting of multi-input multi-output process parameters and plays an important role in manufacturing because of high efficiency, good weld quality, low production cost, easy to realize automation, etc. The welding process parameters plays an important role in controlling weld bead quality; therefore, choosing an appropriate set of welding parameters is required for obtaining good weld bead. In addition, new materials are developed to increase properties and response parameters depend on new materials and input process parameters. In the present work, AISI 321 steel of 10 mm thickness is used for experimentation joined using AISI 308L filler rod of 1.2 mm diameter by controlling four input process parameters, viz welding voltage, welding speed, wire feed rate, and gas flow rate. The weld bead geometry parameters such as bead height, bead width, and bead penetration and mechanical properties such as tensile strength and hardness are considered as output parameters. The mathematical models are developed and tested using analysis of variance. The effects of process parameters on output parameters and microstructure are found out. Furthermore, the thermo-mechanical simulations are carried out using ANSYS simulation software which predicts the temperature and stresses distribution in the weldment.